Levocetirizine Modulates Lymphocyte Activation in Patients With Allergic Rhinitis - Fadia Mahmoud; Nirmina Arifhodzic; David Haines; Ladislav Novotney (Elsevier, 2008)
Levocetirizine, a second generation non-sedating antihistamine that blocks the H1 histamine receptor, may exhibit immunoregulatory properties that augment its primary pharmacological mechanism. To investigate this possibility, 13 Kuwaiti seasonal allergic rhinitis (SAR) patients were treated with levocetirizine for four weeks in comparison with a 7-member placebo-treated control group, followed by clinical evaluation and flow cytometric analysis of peripheral venous blood for inflammatory cell and lymphocyte subpopulation profiles. Relative to the controls, levocetirizine-treated patients exhibited an expected reduction in early phase allergic symptoms, including sneezing (P<0.001), nasal itching (P<0.01), nasal congestion, and running nose (P<0.001); reduced percentages of eosinophils (P<0.05); and three subpopulations of activated T lymphocytes: CD4+CD29+, CD4+CD212+, and CD4+CD54+ (P<0.05). Levocetirizine treatment also correlated with a significant increase in the percentage of CD4+CD25+ T cells (P<0.001). The ability of levocetirizine to reduce percentage representation of cell phenotypes known to contribute to inflammatory tissue damage (eosinophils, CD4+CD29+, CD4+CD212+, and CD4+CD54+) and expand percentages of CD4+CD25+, which may include protective immunoregulatory (Treg) cells, indicates that the drug has pharmacological potential beyond the immediate effects of H1 histamine-receptor inhibition. Although the present data does not define a therapeutic mechanism, the results reported here establish important trends that may be used to guide future mechanistic examination of immunoregulatory capacity of H1 inhibitors. Keywords:: T cell, peripheral blood, rhinitis, regulatory T cell (Treg), interleukin-12 receptor β1